Fever - Banks, Maya (New York : Berkley Books, 2013)
Jace, Ash, and Gabe have been best friends and successful business partners for years. They're powerful, they're imposing, they're irresistibly sexy, and Jace and Ash share everything-- including their women. When they meet Bethany, Jace begins to feel things he's never experienced before: jealousy, and a powerful obsession that threatens him, overwhelms him-- and excites him beyond control. Jace isn't sharing Bethany. He's determined to be the only man in her life, and it's jeopardizing a lifelong friendship with Ash ..
Keywords: Man-woman relationships -- Fiction; Erotic fiction